Perceived life balance, cultural experience, and academic outcomes: A comparative study of first-generation students in South Africa and Canada - Elizabeth Sipiwe Ndofirepi; Raazia Moosa; Maureen J. Reed; Mandivavarira Maodzwa-Taruvinga (University of Johannesburg, 2023)
Not much is known about how first-generation students' cultural experiences, resourcefulness, resilience and their belief that they are able to balance multiple roles affects their academic success. In this North-South comparative study, we examined the impact of culture and perceived ability to balance multiple academic and non-academic roles (balance belief) on academic outcomes experienced by first-generation and non-first-generation students in Canada and South Africa. We also identified the relationship between culture, balance belief, student resilience and resourcefulness and academic outcomes (grades, adjustment and academic self-efficacy). While academic behaviours were similar across countries and similar between students who are and are not first-generation, some non-academic roles differed. Further, for all students, greater balance belief had a small positive effect on grades, university adjustment and academic self-efficacy. When balance belief was combined with students' academic resourcefulness, predictions of grades, especially for first-generation students from South Africa, were improved. Interventions that improve balance belief may aid students in each country; but understanding cultural experiences related to resourcefulness and resilience is importance since their association with balance belief varies between country and first-generation status.